ECOLOGICAL WISDOM IN WANGSALAN AS AN EFFORT TO STRENGTHEN CHARACTER EDUCATION WITH CONSERVATION-MINDED - Nur Hanifah Insani (Aksara, 2020)
Literature has close relationship with the environment. Literature also has an important role in the preservation of environment. Research with this qualitative approach aims to explain the representation of ecological wisdom in the wangsalan as an effort to strengthen character education with conservation-minded. Data of words, phrases, clauses and sentences are analyzed using inter-textual and functional pragmatic methods. The results of this study are: (1) The ecological elements contained in the wangsalan can be divided into five categories, are flora (for example, roning mlinjo:so; janur kuning:pupus; kembang tebu:gleges), fauna (example, wader bungkuk:urang; kapi jarwa:kethek; ayam wana:bekisar), nature (for example, udan riris:grimis; sedhang arga:tlaga, teja bengkok:kluwung), geography/area (example, kutha Gudheg:Yogyakarta; kulone Banjar Patoman:Tasik; peken alit:wande), and cultural outcomes (example, jangan gori:gudheg; gayung sumur:timba; nyaron bumbung:angklung); (2) Every lexicon in wangalan has a philosophy that consist character education, such as love of peace or tends to avoid conflict with others and the environment, not impose, kindness, politeness, patience, and respect for others. From the results of the research is known that wangsalan contains ecological wisdom that needs to be preserved. In addition, this ecological study in the wangsalan can be used as an alternative source to strengthen character education with conservation-minded.Keywords: wangsalan; ecological wisdom; character education; conservation mindedSastra memiliki keterkaitan erat dengan lingkungan. Sastra juga memiliki peran penting akan kelestarian lingkungan. Penelitian dengan pendekatan kualitatif ini bertujuan untuk menjelaskan wujud kearifan ekologi dalam wangsalan sebagai representasi suatu pendidikan karakter. Data yang berwujud kata, frasa, klausa, dan kalimat dianalisis menggunakan metode intertekstualitas dan pragmatik fungsional. Hasil penelitian ini adalah: (1) unsurunsur ekologi yang terdapat dalam wangsalan dapat terbagi menjadi lima kategori, yaitu flora (misalnya, roning mlinjo:so; janur kuning:pupus; kembang tebu:gleges), fauna (misalnya, wader bungkuk:urang; kapi jarwa:kethek; ayam wana:bekisar), alam (misalnya, udan riris:grimis; sedhang arga:tlaga, teja bengkok:kluwung), letak geografi/daerah (misalnya, kutha Gudheg:Yogyakarta; kulone Banjar Patoman:Tasik; peken alit:wande), serta hasil budaya (misalnya jangan gori:gudheg; gayung sumur:timba; nyaron bumbung:angklung); (2) setiap leksikon pembentuk wangsalan memiliki filosofi pendidikan karakter, seperti cintadamai/cenderung menghindari konflik dengan lingkungan, tidak memaksakan diri, sifat ramah, santun, sabar, serta menghargai orang lain. Dari hasil penelitian dapat diketahui bahwa wangsalan mengandung kearifan ekologi yang perlu untuk terus dilestarikan. Selain itu, kajian ekologi dalam wangsalan ini dapat dijadikan sebagai alternatif sarana pendidikan karakter.Kata kunci: wangsalan; kearifan ekologi; pendidikan karakter; wawasan konservasi